Biomarkers of Osteosarcoma, Chondrosarcoma, and Ewing Sarcoma - Evola, Francesco R.; Costarella, Luciano; Pavone, Vito; Caff, Giuseppe; Cannavò, Luca; Sessa, Andrea; Avondo, Sergio; Sessa, Giuseppe (Frontiers in Pharmacology, 2017)
Osteosarcoma is the most frequent malignant bone neoplasm, followed by chondrosarcoma and Ewing sarcoma. The diagnosis of bone neoplasms is generally made through histological evaluation of a biopsy. Clinical and radiological features are also important in aiding diagnosis and to complete the staging of bone cancer. In addition to these, there are several non-specific serological or specific molecular markers for bone neoplasms. In bone tumors, molecular markers increase the accuracy of the diagnosis and assist in subtyping bone tumors. Here, we review these markers and discuss their role in the diagnosis and prognosis of the three most frequent malignant bone neoplasms, namely osteosarcoma, chondrosarcoma, and Ewing sarcoma.